2012
DOI: 10.1021/bi201818c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Inducible Nitric Oxide Synthase Auto-S-nitrosation and Inactivation

Abstract: Nitric oxide (NO), the product of the nitric oxide synthase (NOS) reaction, was previously shown to result in S-nitrosation of the NOS Zn2+-tetrathiolate and inactivation of the enzyme. To probe the potential physiological significance of NOS S-nitrosation, the inactivation timescale of the inducible NOS isoform (iNOS) was determined and found to directly correlate with an increase in iNOS S-nitrosation. A kinetic model of NOS inactivation in which arginine is treated as a suicide substrate was developed. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…For instance, if genomic damage exceeds the ability of the cell to repair its DNA, then inhibition of Sirt1 deacetylase activity by S-nitrosation would increase p53 acetylation and promote apoptosis (45). Interestingly, we recently observed a similar dependence on physiological GSH concentrations for iNOS inhibition by S-nitrosation of the iNOS Zn 2ϩ -tetrathiolate (46). In summary, we have demonstrated that Sirt1 is directly modified and inhibited by cysteine S-nitrosation.…”
Section: Journal Of Biological Chemistry 25403mentioning
confidence: 51%
“…For instance, if genomic damage exceeds the ability of the cell to repair its DNA, then inhibition of Sirt1 deacetylase activity by S-nitrosation would increase p53 acetylation and promote apoptosis (45). Interestingly, we recently observed a similar dependence on physiological GSH concentrations for iNOS inhibition by S-nitrosation of the iNOS Zn 2ϩ -tetrathiolate (46). In summary, we have demonstrated that Sirt1 is directly modified and inhibited by cysteine S-nitrosation.…”
Section: Journal Of Biological Chemistry 25403mentioning
confidence: 51%
“…The abundance of SNO-GRK2 and SNO-β-arrestin2 is diminished in eNOS -/-mice and enhanced in GSNOR -/-mice (28, 34); eNOS and GSNOR thus promote S-nitrosylation and denitrosylation of these proteins, respectively, through the intermediacy of GSNO. eNOS also binds dynamin (46), but whether S-nitrosylation is mediated directly by a transnitrosylase activity of NOS (48,49) or via GSNO is not known. GSNOR -/-mice further exhibit increases in cardiac output under basal conditions, reflecting marked peripheral vasodilation (29) as well perhaps as pronounced myocardial angiogenesis that results from stimulatory S-nitrosylation of HIF-1α under normoxic conditions (35).…”
mentioning
confidence: 99%
“…Thus, it is feasible that negative feedback onto S-nitrosylation-dependent NF-jB inactivation should be taken into account. In this mechanism, inactivation of IKK/NF-jB by S-nitrosylation could downregulate iNOS expression and the associated S-nitrosylation activity, an effect reinforced by the fact that iNOS itself is susceptible to inactivation by S-nitrosylation (117,163). As a result, NF-jB activation may be equilibrated in cells, and the levels of NF-jB-induced cytokines and endothelial adhesion molecules (vascular cell adhesion protein 1, intercellular adhesion molecule 1, and E-and P-selectins) sustained for leukocyte extravasation and function.…”
Section: Nf-kb Pathway and S-nitrosylationmentioning
confidence: 99%